2015
DOI: 10.1007/s11738-015-1807-x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of citric acid and isocitric acid in the diurnal cycle of carboxylation and decarboxylation in the common ice plant

Abstract: In this paper we analyzed changes in the concentration of the three carboxylic acids (malic acid, citric acid and isocitric acid) during the salinity-induced C 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This conclusion is further supported by another study in ice plant in which malate, citrate and isocitrate levels and CAM-relevant enzyme activities were measured for the same CAM-inducing conditions 5 . The authors reported malate and citrate levels of up to 27.5 mM and 29.4mM, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…This conclusion is further supported by another study in ice plant in which malate, citrate and isocitrate levels and CAM-relevant enzyme activities were measured for the same CAM-inducing conditions 5 . The authors reported malate and citrate levels of up to 27.5 mM and 29.4mM, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…51,52 However, CO 2 can also be fixated and stored in the form of other organic acids such as citrate, isocitrate, fumarate and succinate. 53,54 During the daytime, when the stomata are closed, the organic acids stored in the vacuole are released into the cytosol and decarboxylated, releasing CO 2 that is converted into carbohydrates by the Calvin-Benson (C 3 ) cycle. 51,52 In this review, this type of photosynthetic metabolism will be addressed on some occasions because it is activated in response to several stresses associated or not with thermal changes.…”
Section: Limit Of Heat Tolerance In Plantsmentioning
confidence: 99%
“…Encouraged by that fact, in our previous study we tested if a shift towards CAM photosynthesis performance may be initiated with elevated Cd concentrations as well. The ∆-malate (difference in malate concentration between the beginning and end of the light phase of photoperiod), as well as 13 C discrimination analysis both of which are the hallmarks of functional CAM, revealed no remarks of CAM presence in Cd-treated C 3performing plants, con rming that Cd does not belong to the group of abiotic stress factors capable of inducing CAM photosynthesis (Nosek et al 2019).…”
Section: Discussionmentioning
confidence: 96%